Keratinocyte Skin Cancers in General Surgery: The Impact of Anaesthesia, Trainee Supervision, and Choice of Reconstruction - William McSweeney; Matthew Leaning; Darius Dastouri (Journal of Skin Cancer)
Background. Keratinocyte skin cancers are common in Australia, incurring disproportionately high health expenditure in comparison with mortality. General surgeons often excise these lesions as day-surgery. Balancing individual complexities of these cancers with trainee supervision and health expenditure is key to deliver efficacious care and maintain day-surgery volume for patients during a pandemic. Methods. A retrospective, cross-sectional study was performed, examining 414 procedures from January 2019 to December 2020. Pathology was reviewed, and benign lesions excluded. Complete excision was based on 5 mm margins for squamous cell carcinoma (SCC), 0.5 mm microscopic margins for low-risk basal cell carcinoma (BCC) subtypes, and 3 mm for high-risk. Results of trainee-performed local anesthetic (LA) excision and general anesthetic (GA) excision (consultant scrubbed) were compared. Results. 288 excisions were reviewed for completeness, location, and reconstruction modality. 69% were BCC (199), and 31% were SCC (89). These were excised under GA (72.5%) and LA (27.5%). 25.6% of BCC excisions were “close,” and 22.6% were “positive” under GA, whilst 31% were “close” and 15.5% were “positive” under LA. 52.8% of SCC excisions were “close,” and 7.8% were “positive” under GA, compared with 42.8% “close” and 9.5% “positive” under LA. Complex reconstruction (skin graft, flap) was more common under GA (38% SCC and 36.1% BCC), but occurred at a modest rate under LA (22% BCC and 28.5% SCC). Conclusions. The results confirm that comparable margins and reconstruction options are achievable when excising keratinocyte cancers under LA by surgical trainees. This is fundamental in cost and timesaving, as well as reducing risk of aerosolisation of virus during GA, in a pandemic.